Gambaran Infeksi Telur Cacing Pada Anak SD Di Desa Karang Anyar Kecamatan Kemiri Kabupaten Tangerang - Siti Husniah; Zahara Fadilla (Jurnal Ventilator, 2023)
Worms are one of the Neglected Tropical Disease (NTD) or neglected tropical diseases in Indonesia, this disease can attack all ages but mostly attacks children of unschooled age and elementary school age. This helminthic disease generally attacks people in developing countries, especially in people with low socioeconomic in rural areas. Poor environmental sanitation accompanied by an unhealthy lifestyle of the community is one of the factors in the ease of breeding worms. The purpose of this study was to determine the picture of worm egg infection in the feces of elementary school children in Karang Anyar Village, RT/01, RW/01, Kemiri District, Tangerang Regency. This research method was carried out by conducting fecal sampling in Karang Anyar Village RT/01 RW/01, Kemiri District, Tangerang Regency and examination of fecal samples by sedimentation method. The results of the examination of worm eggs in feces obtained negative results from 21 fecal samples.